Volar Plate Fixation in Patients Older Than 70 Years with AO Type C Distal Radial Fractures: Clinical and Radiologic Outcomes - Piuzzi, Nicolas S.; Zaidenberg, Ezequiel E.; Duarte, Matias Pereira; Boretto, Jorge G.; Donndorff, Agustin; Gallucci, Gerardo; De Carli, Pablo (Journal of Wrist Surgery, 2017)
Introduction Treatment of unstable distal radial fractures (DRFs) in elderly patients is controversial, and considering the increasing life expectancy, their appropriate treatment is of growing importance. Our aim was to analyze the clinical and radiologic outcomes in the elderly patients with AO type C DRF treated with volar locking plate (VLP).Materials and Methods Between 2007 and 2011, 572 DRFs were operated on in our hospital with open reduction and internal fixation with VLP. Of these, only 64 patients (66 DRFs) met the selection criteria (AO type C DRF, age > 70 years, minimum 12-month follow-up). Mean follow-up was 28 months. Outcome assessment included range of motion, grip strength, VAS pain, Mayo Clinic Score, and DASH score. Analysis of pre- and postoperative radiographs was performed. Complications were recorded. Statistical analysis was performed comparing the results with the contralateral side.Results Mean postoperative range of motion of the injured wrist compared with the control contralateral side was 86% for flexion (p < 0.001), 92% for extension (p < 0.001). The average DASH was 12. Mayo Clinic Wrist Score showed 43 excellent results, 15 good, 4 satisfactory, and 4 poor. Articular step-offs were reduced in 34 of 38 wrists. Five (7%) patients required plate removal.Conclusion The treatment of articular DRF (AO type C) with VLP in the elderly patients achieved greater than 90% of the wrist range of motion and grip strength with no residual pain in greater than 90% of the patients.Level of Evidence Therapeutic IV, case series.
Keywords: distal radial fracture; internal fixation; volar plate fixation; elderly